The effects of core strengthening and stability exercises on various fitness parameters of collegiate streetdancers - Delos Reyes, Joanna Marie B. 2001-; Valleser, Christian Wisdom M. MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
This study focuses on the significance of physical fitness for streetdancers, given the physical demands of their training and performances. The incorporation of core strengthening and stability exercises into their training was explored as a means to enhance core muscle strength, core muscle endurance, and dynamic balance. Such improvements were hypothesized to positively impact dance performance and reduce injury risk, ultimately contributing to the longevity of streetdancers. Specifically, this experimental research evaluates the impact of a 4-week core training program alongside regular dance training for collegiate streetdancers through comparison of their pre-test and post-test scores. A total of five (5) collegiate streetdancers aged 17 to 25, all with a minimum of six (6) months of dance training, and no previous injuries, were tested through 7-stage abdominal strength test, McGill's torso muscular endurance test, and Y balance test. The mean scores for core strength, core endurance (except trunk extensor endurance), and dynamic balance increased during post-test. However, these were not statistically significant (p > 0.05), except for the trunk flexor (p = 0.006) and right lateral trunk (p = 0.006). Cohen’s d showed medium effect on both the trunk flexor (d = 0.45) and right lateral trunk (d = 0.64) endurance. Additionally, the study observed non-adherence among participants, and identified time constraints and fatigue as significant factors. This emphasizes the need for a well-regulated fitness and skills training program to preserve the health of streetdancers and mitigate such incidence.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Keywords: Exercise -- Physiological aspects; Muscle strength; Physical fitness -- Testing; Dancers